ChemInform Abstract: Iridium‐Catalyzed Asymmetric Allylic Substitutions with Bulky Amines/Oxidative Double Bond Cleavage — Entry into the Reetz Synthesis of Amino Alcohols. Issue 25 (June 2016) - Seehafer, Kai; Malakar, Chandi C.; Bender, Markus; Qu, Jianping; Liang, Chen; Helmchen, Guenter
Abstract: Branched allylic amines are synthesized and transformed into N‐protected amino aldehydes.